2020
DOI: 10.1038/s41398-020-00941-z
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic evidence and overlapped brain functional connectivities for the association between chronic pain and sleep disturbance

Abstract: Chronic pain and sleep disturbance are highly comorbid disorders, which leads to barriers to treatment and significant healthcare costs. Understanding the underlying genetic and neural mechanisms of the interplay between sleep disturbance and chronic pain is likely to lead to better treatment. In this study, we combined 1206 participants with phenotype data, resting-state functional magnetic resonance imaging (rfMRI) data and genotype data from the Human Connectome Project and two large sample size genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…We found that mental health symptoms were the largest risk factors for constant pain in the long-term quarantine population, indicating that pain could be a consequence of those mental health symptoms (effect b in Figure 1 ). These basic findings are consistent with research showing that psychological factors that are frequently comorbid with chronic pain also predispose patients to the development of chronic pain [ 4 , 6 ] and may in turn exacerbate and worsen pain symptoms. No social obligations and the lack of communication during quarantines did not result in more sleep; conversely, most people actually experienced worse quality sleep due to their damaged sleep schedules, stress and anxiety [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that mental health symptoms were the largest risk factors for constant pain in the long-term quarantine population, indicating that pain could be a consequence of those mental health symptoms (effect b in Figure 1 ). These basic findings are consistent with research showing that psychological factors that are frequently comorbid with chronic pain also predispose patients to the development of chronic pain [ 4 , 6 ] and may in turn exacerbate and worsen pain symptoms. No social obligations and the lack of communication during quarantines did not result in more sleep; conversely, most people actually experienced worse quality sleep due to their damaged sleep schedules, stress and anxiety [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although it is widely known that pain can cause mental health symptoms and sleep disturbances, we also need to realize that the interaction is bidirectional. Sleep disturbance could exacerbate pain via neurophysiological processes that modulate pain signaling at supraspinal and spinal levels [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disruption and chronic pain are comorbid disorders, with a survey of individuals suffering from fibromyalgia putting non-restorative sleep before pain in order of symptom severity ( 10 , 35 ). Therefore, both should be assessed when considering treatments/interventions and healthcare costs in people with chronic pain ( 36 ). Since there is evidence for the co-occurrence of sleep disturbance and chronic pain ( 10 ), treatment with neuromodulation may be a beneficial therapy for patients with both disorders, as suggested by our results.…”
Section: Discussionmentioning
confidence: 99%
“…The role of impaired sleep in chronic pain is gaining more scientific focus in recent years. Accumulating evidence suggests that maladaptive sleep hampers both neural and molecular control mechanisms (e.g., Haack et al, 2020 ; Sun et al, 2020 ). Our results lend additional support for the relation between impaired neural connectivity and sleep disturbance, and in addition, highlight the role of affective attention in pain chronicity.…”
Section: Discussionmentioning
confidence: 99%